Emphysematous osteomyelitis: A rare case report - Siddartha Guru; Navami Guru; Rezhan Hussein (IDCases)
Emphysematous osteomyelitis is a rare entity that characteristically presents with intraosseous gas and positive bone cultures with gas-forming bacteria. We present a case of a 63-year-old woman who presented with lower back pain, decreased appetite, and unintentional weight loss over three weeks. Thoracic spine Computerized tomography image showed an ill-defined lytic lesion containing gas in the T12 vertebral body with anaerobic bone cultures, which grew Clostridium septicum. There was concern for possible complication of meningitis with abnormal CSF studies but no bacterial growth, though lumber puncture was done after being on antibiotics for five days. She was found to have underlying metastatic colon cancer as well. She was treated with six weeks of ceftriaxone and metronidazole and then transitioned to oral amoxicillin-clavulanic acid while on chemotherapy.